Physical activity and inactivity in Girl Scout Junior troop meetings - Ornelas, Samuel; Rosenkranz, Richard R. (My University, 2009)
Purpose: To describe the environmental context, physical activity, and inactivity levels in Girl Scout Junior troop meetings. Methods: Forty-two girls (mean age 10.8 ± 1.2) from four troops wore accelerometers during 28 meetings. Physical activity (PA) and sedentary behavior (SED) were assessed during a six-month period. Minutes spent in sedentary, light, moderate, and vigorous PA were summed and averaged. Direct observation measures assessed the environmental context of activity/inactivity. Results: In an average troop meeting, girls spent 94.4 min of time in SED, 26.3 min in light physical activity (LPA), and 2.0 min in moderate-to-vigorous physical activity (MVPA). There was no significant difference for time spent in PA at various levels among girls of different socio-economic status, racial/ethnic background, or weight status (F [3,238] <1.0, p >.05). Troop leaders were more likely to discourage PA (0.6% of time) than to promote PA (0.0%), and no PA related educational content was observed. Conclusion: Girls accumulated two min MVPA, and >90 min SED per meeting. Based on our observations, these troop meetings currently are missing opportunities to contribute positively to the health and fitness of attending girls. Interventions providing opportunities for enjoyable PA specifically catering to needs and interests of girls are warranted.
Keywords: Girl Scouts; Accelerometer; Sedentary behavior; Physical activity; Childhood obesity